2020
DOI: 10.2147/orr.s259337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Three Femoral Stem Designs Without Corrosion: A Review of 2095 Stems</p>

Abstract: Introduction Corrosion at the head–neck interface of modular components in total hip arthroplasty (THA) has been reported as a cause of failure of modern total hip replacement implants. While this method of failure has been well described, it remains poorly understood. The purpose of this study is to review the three most commonly used uncemented femoral stems at our institution over the last fifteen years and to correlate any established risk factors with rates of revision, particularly corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…2,[11][12][13] As such, surgeon efforts to minimise the risk of trunnionosis are largely limited to implant selection, fuelling numerous implantspecific clinical and retrieval studies that have highlighted discrepancies in prosthesis performance with respect to head-neck corrosion. 4,14,15 Prior studies have identified a femoral component design from a single manufacturer with an increased propensity for gross trunnion failure (Figure 1). [16][17][18][19][20][21][22][23][24] These events involve either fracture of the trunnion or dissociation of femoral head from the trunnion (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[11][12][13] As such, surgeon efforts to minimise the risk of trunnionosis are largely limited to implant selection, fuelling numerous implantspecific clinical and retrieval studies that have highlighted discrepancies in prosthesis performance with respect to head-neck corrosion. 4,14,15 Prior studies have identified a femoral component design from a single manufacturer with an increased propensity for gross trunnion failure (Figure 1). [16][17][18][19][20][21][22][23][24] These events involve either fracture of the trunnion or dissociation of femoral head from the trunnion (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…2,1113 As such, surgeon efforts to minimise the risk of trunnionosis are largely limited to implant selection, fuelling numerous implant-specific clinical and retrieval studies that have highlighted discrepancies in prosthesis performance with respect to head-neck corrosion. 4,14,15…”
Section: Introductionmentioning
confidence: 99%